Violence and the competition for sovereignty in Cherokee Country, 1829–1835. Issue 2 (3rd May 2016) - Pratt, Adam J.
ABSTRACT: Beginning in 1829 with the discovery of gold and ending in 1835 with the ratification of the Treaty of New Echota, three political entities waged a struggle for political sovereignty over the Cherokee Nation. The Cherokees, of course, had their national self-determination at stake. They referenced treaties with the U.S. government that reaffirmed their status as an independent nation, but also looked to the federal government and its commitments in those same treaties to help the Cherokees uphold their territorial integrity. In this formulation, which the Supreme Court verified, the federal government reigned supreme. The ambiguous nature of American federalism also made it possible for the state of Georgia to claim sovereignty. Beginning in 1830, the state used violence against Cherokees under the guise of bringing social order to a lawless region. The vehicle for creating state authority, the Georgia Guard, used violence as a way of making life untenable for those the state saw as less than desirable. Criminals, especially members of the Pony Club, and Cherokees, were deliberately targeted by the Guard. Federal authorities eventually relented and relied on state figures to help pave the way for the implementation of Removal. By doing so, they effectively ceded political sovereignty to the state.